Role of Instagram Beauty Influencers in Shaping Body Image and False Consciousness among Female University Students - Maha Aejaz; Shajee Hassan (Wah Academia Journal of Social Sciences, 2026)
Instagram being the popular social media platform has drastically changed the way people see beauty, femininity, and self-worth within contemporary digital culture. This study examines the role of Instagram beauty influencers in shaping body image and false consciousness among female university students in Pakistan. The research investigates how exposure to influencer content through reels, stories, pictures, and highlights, affects women’s perceptions about themselves, consumer motivations, and awareness of unrealistic beauty ideals, by using Cultivation Theory, Social Comparison Theory and Socio-Cultural Theory as base. A quantitative, cross-sectional survey was conducted to 300 female students from the University of Sargodha and the University of the Punjab, Lahore. Data were analyzed using demographic, statistical and descriptive analysis. Results showed that higher exposure to influencer content, especially dynamic formats like reels and stories significantly increases body dissatisfaction and self-comparison tendencies. Younger respondents (18–25 years) reported greater insecurity as compared to the older participants, while education and residence had negligible effects, suggesting that influencer culture operates across demographic boundaries. Respondents also demonstrated opposite views simultaneously, admiring influencer beauty while recognizing its unattainable nature. The findings underscore Instagram’s pervasive influence as both a cultural and psychological force, reinforcing appearance-driven identities and consumption patterns. The study stresses that media literacy is need of the hour to mitigate the internalization of harmful beauty ideals among young women in digital Pakistan.